1999
DOI: 10.4141/p98-117
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of self-compatibility and flower morphology in an inter-specific buckwheat hybrid

Abstract: . 1999. Inheritance of self-compatibility and flower morphology in an inter-specific buckwheat hybrid. Can. J. Plant Sci. 79: 483-490. This study was conducted to determine the inheritance of selfcompatibility and homomorphic flower type when the wild species Fagopyrum homotropicum was crossed with common buckwheat (F. esculentum). Unidirectional interspecific hybrids between cultivated F. esculentum Moench. (common buckwheat) and its wild relative F. homotropicum were produced after controlled pollination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 8 publications
5
37
0
Order By: Relevance
“…In Fagopyrum genus, F. homotropicum and F. esculentum are the two most closely related species within the cymosum clade or group (Ohnishi and Matsuoka 1996;Yasui and Ohnishi 1998). Fertile hybrids between F. homotropicum diploid and F. esculentum (Campbell 1995;Wang and Campbell 1998;Woo et al 1999b) formed bivalents at meiosis (data not shown), confirming the close relationship between F. esculentum and F. homotropicum diploid. When homologous chromosomes of F. homotropicum tetraploid were not present in the F 1 hybrids, homoeologous chromosome pairing probably occurred between the three genomes, one from F. esculentum and two from F. homotropicum, resulting in gametes with uneven chromosome numbers and/or chromosome loss.…”
Section: Mechanisms Of Chromosome Doubling and Eliminationsupporting
confidence: 50%
See 1 more Smart Citation
“…In Fagopyrum genus, F. homotropicum and F. esculentum are the two most closely related species within the cymosum clade or group (Ohnishi and Matsuoka 1996;Yasui and Ohnishi 1998). Fertile hybrids between F. homotropicum diploid and F. esculentum (Campbell 1995;Wang and Campbell 1998;Woo et al 1999b) formed bivalents at meiosis (data not shown), confirming the close relationship between F. esculentum and F. homotropicum diploid. When homologous chromosomes of F. homotropicum tetraploid were not present in the F 1 hybrids, homoeologous chromosome pairing probably occurred between the three genomes, one from F. esculentum and two from F. homotropicum, resulting in gametes with uneven chromosome numbers and/or chromosome loss.…”
Section: Mechanisms Of Chromosome Doubling and Eliminationsupporting
confidence: 50%
“…Efforts to improve common buckwheat have been made through interspecific hybridization between common buckwheat and related species F. cymosum (Ujihara et al 1990;Suvorova et al 1994;Hirose et al 1995;Rumyantseva et al 1995;Woo et al 1999a) and F. tataricum (Morris 1951;Samimy 1991;Hirose et al 1995;Samimy et al 1996;Chen 1998;Wang and Campbell 1998;Woo 1998;Fesenko et al 2001;Wang et al 2002a). However, success has been limited due to sterility of the hybrids.…”
mentioning
confidence: 99%
“…This inheritance pattern was first proposed for the genus Primula, where there is evidence that three to five, or more, linked genes occur (Ernst, 1955;Dowrick, 1956;Lewis and Jones, 1992;Kurian and Richards, 1997;Barrett and Shore, 2008). There is more limited evidence supporting the occurrence of a supergene in lineages outside the Primulaceae that have independently evolved distyly, including Fagopyrum (Woo et al, 1999;Matsui et al, 2003;Fesenko et al, 2006;Wang et al, 2005) and Turnera, where the inheritance of self-compatible homostyles has been investigated (Shore and Barrett, 1985;Barrett and Shore, 1987;Tamari et al, 2001Tamari et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Self-incompatibility and self-compatibility are controlled by the S locus, and the self-compatibility allele S h dominates the self-incompatibility allele, s 17,11 . F 1 plants were produced by a cross between early leaf-senescence self-incompatible pin plants of KS1 and wild-type self-compatible long-homostyle plants of sco-ASH and sco-KNY.…”
Section: Estimation Of Number Of Genes Controlling Early Leaf-senescencementioning
confidence: 99%